Structural Shifts and Information Density of Complex Noun Phrases in Sinta 2 Abstract: A Translation Study - Syahmiarni Syahmiarni; Veni Roza; Widya Syafitri (Journal of English Education Program (JEEP), 2026)
This study examines structural shifts and information density in the translation of Complex Noun Phrases (CNPs) from Indonesian into English in Sinta 2-accredited bilingual journal abstracts. Grounded in Catford's (1965) framework of structural shift and Halliday's (1985) lexical density formula as a measurement instrument for information density, the study addresses three research questions: (1) how CNPs are structurally restructured in Indonesian-English translation; (2) what linguistic mechanisms characterize those structural shifts; and (3) how structural shifts relate to information density in translated CNPs. A descriptive qualitative design was employed, with data consisting of 110 CNPs extracted from fifteen purposively selected bilingual abstracts across five Sinta 2 ELT and linguistics journals published between 2021 and 2026. Findings reveal that structural shifts occurred consistently across all fifteen abstracts, with four predominant mechanisms: modifier-head reordering (43.6%), modification pattern change (26.4%), constituent expansion or reduction (17.3%), and grammatical relation transformation (12.7%). Information density effects were variable: some shifts increased density by compressing meaning into compact English premodifier stacks, others preserved informational equivalence, and a smaller number reduced density when nominalized source-language concepts were merged into more general target-language expressions. These findings reveal a tension in academic translation between grammatical naturalness and conceptual precision, contributing to translation studies by integrating structural and functional perspectives on Indonesian-English academic translation.